Cervical cancer in Asian countries: epidemiology, risk factors and challenges - Sultana, Sayeeda; Khatun, Sabera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical cancer is one of the leading causes for cancer mortality in women worldwide especially in Asian region where, preventive strategies are underdeveloped, particularly in low-and middle-income countries (LMICs). The global cervical cancer burden and characteristics vary significantly, particularly between high-income (HICs) and LMICs. To obtain a systematic review of 20 peer-reviewed newspaper articles published within the range from 2010 to 2023, accessed through PubMed, Scopus and Google Scholar. Studies related to incidence, mortality, preventive measures and healthcare disparity in Asian countries were included. Findings from the review demonstrate that cervical cancer is inordinate burdened in South-Central Asia, with nearly 48% of the region’s estimated cases occurring between India and Bangladesh. The screening coverage is a cause for concern, with only 33% of women in India and 7.5% of women in Bangladesh getting screened regularly. In stark contrast, HPV vaccination coverage is below 30% in most LMICs with over 70% in Japan and South Korea. Low levels of healthcare infrastructure, late-stage diagnoses, and cultural barriers to vaccine uptake represent some of these key challenges. Effective HPV vaccination and screening programs can prevent cervical cancer (CC) cases and deaths, but the availability and coverage of these interventions in Asian LMICs are uncertain. Better prevention and treatment can be achieved through improved healthcare infrastructure, but first cultural barriers need to be overcome.